2019
DOI: 10.1021/acsomega.8b02766
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Rheological Cross-Analysis of Polyester Polyol Cure Behavior: Role of Polyester Secondary Hydroxyl Content

Abstract: The sol–gel transition of a series of polyester polyol resins possessing varied secondary hydroxyl content and reacted with a polymerized aliphatic isocyanate cross-linking agent is studied to elucidate the effect of molecular architecture on cure behavior. Dynamic rheology is utilized in conjunction with time-resolved variable-temperature Fourier-transform infrared spectroscopy to examine the relationship between chemical conversion and microstructural evolution as functions of both time and temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…This is because neem oil has no reactive hydroxyl group, which reduces the structure of urethane, urea, amide II and, amide III ( Table 3 ). The previous study also indicated polyol with secondary hydroxyl groups can increase the crosslinking density of PU resin [ 34 ]. The results demonstrate that NOG can enhance the solvent resistance of bio-based PU foam.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because neem oil has no reactive hydroxyl group, which reduces the structure of urethane, urea, amide II and, amide III ( Table 3 ). The previous study also indicated polyol with secondary hydroxyl groups can increase the crosslinking density of PU resin [ 34 ]. The results demonstrate that NOG can enhance the solvent resistance of bio-based PU foam.…”
Section: Resultsmentioning
confidence: 99%
“…The densities of O1-2, O2-2 and, O3-2 are 116.2, 81.4 and 70.8 kg/m 3 , respectively. This result is due to NOG polyol with secondary hydroxyl groups which helps the PU resin to cure rapidly and maintain the foam’s structural integrity during the foaming process [ 34 ]. Figure 4 displays the PU foam micrographs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction rate was evaluated by monitoring the conversion of NCO groups ($2260 cm À1 ) using Fourier-transform infrared spectroscopy (FTIR), 39 which is a technique widely used in the synthesis of polyurethane. [40][41][42][43] The polyurethanes synthesized in green solvents achieved similar NCO conversion with time to the polyurethane synthesized in NMP (see ESI †). However, at intermedium reaction times NMP and GVL achieved higher conversion grades than CY.…”
Section: Resultsmentioning
confidence: 99%